Identification of a Novel 19-bp Deletion Mutation in LTBP4 Using Exome Sequencing in Two Siblings with Autosomal Recessive Cutis Laxa Type 1C - Gupta, Neerja; Langeh, Nitika; Sridharan, Aparajit; Kabra, Madhulika (Journal of Pediatric Genetics, 2020)
Autosomal recessive type I cutis laxa is genetically heterogeneous. Biallelic mutations in latent transforming growth factor β-binding protein 4 (LTBP4; MIM*604710) lead to type 1C cutis laxa due to nonsense, frameshift, single base pair indels, or duplication mutations. In this report, we describe the first Indian family with cutis laxa as a result of a novel 19 base pair homozygous deletion leading to premature termination of short isoform LTBP-4S.
Keywords: LTBP4; autosomal recessive cutis laxa; latent transforming growth factor